2014
DOI: 10.1007/978-1-4939-1625-2_15
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Phages and Prophages: Genomics, Taxonomy, and Applied Aspects

Abstract: Since this book was originally published in 2007 there has been a significant increase in the number of Salmonella bacteriophages, particularly lytic virus, and Salmonella strains which have been fully sequenced. In addition, new insights into phage taxonomy have resulted in new phage genera, some of which have been recognized by the International Committee of Taxonomy of Viruses (ICTV). The properties of each of these genera are discussed, along with the role of phage as agents of genetic exchange, as therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 220 publications
(161 reference statements)
2
26
0
2
Order By: Relevance
“…Schmieger and co-workers (Schicklmaier et al , 1998; Schmieger, 1999) found that 173 S. enterica serovar Typhimurium isolates released a minimum of 136 functional phages, and the commonly used laboratory Typhimurium isolate LT2 carries four intact, fully functional prophages (Yamamoto, 1967 & 1969; Yamada et al , 1986; Figueroa-Bossi and Bossi, 1999; McClelland et al , 2001). Many studies have also shown that prophage content accounts for a substantial part of the natural variation among Salmonella isolates ( e.g., Reen et al , 2005; Cooke et al , 2007; Drahovska et al , 2007; Rychlik et al , 2008; Fricke et al , 2011; Moreno Switt et al , 2012; Pang et al , 2013; Bobay et al , 2014; Hiley et al , 2014; Switt et al , 2015). …”
Section: Resultsmentioning
confidence: 99%
“…Schmieger and co-workers (Schicklmaier et al , 1998; Schmieger, 1999) found that 173 S. enterica serovar Typhimurium isolates released a minimum of 136 functional phages, and the commonly used laboratory Typhimurium isolate LT2 carries four intact, fully functional prophages (Yamamoto, 1967 & 1969; Yamada et al , 1986; Figueroa-Bossi and Bossi, 1999; McClelland et al , 2001). Many studies have also shown that prophage content accounts for a substantial part of the natural variation among Salmonella isolates ( e.g., Reen et al , 2005; Cooke et al , 2007; Drahovska et al , 2007; Rychlik et al , 2008; Fricke et al , 2011; Moreno Switt et al , 2012; Pang et al , 2013; Bobay et al , 2014; Hiley et al , 2014; Switt et al , 2015). …”
Section: Resultsmentioning
confidence: 99%
“…This genus was recently proposed by Moreno Switt et al (2014). To date, three members (FSL SP-031, FSL SP-038, and FSL SP-049) have been reported, though only the genome of phage FLS SP-031 is fully sequenced, hence the proposed genus "Sp3unalikevirus" [42].…”
Section: "Sp3unalikevirus"mentioning
confidence: 99%
“…Not surprisingly, Salmonella phages are also numerous and varied. The morphology of 177 Salmonella phages was reviewed in 2007 [2] (updated in [55]), with most representatives belonging to the order Caudovirales (tailed phages with a dsDNA genome) and its three families, Siphoviridae, Myoviridae and Podoviridae. A small number of phages representing the families Inoviridae, Leviviridae, Microviridae and Tectiviridae have also been documented.…”
Section: Introductionmentioning
confidence: 99%
“…While phages and prophages of subsp. enterica have been intensively studied (reviewed in [18, 30, 32]), information on phages in other Salmonella subspecies is scarce. In fact, putative prophage sequences were only recently identified in the whole genome sequences of two strains belonging to non- enterica subspecies, i.e.…”
Section: Discussionmentioning
confidence: 99%